2019
DOI: 10.3389/fmicb.2019.00976
|View full text |Cite
|
Sign up to set email alerts
|

The Farnesyltransferase β-Subunit Ram1 Regulates Sporisorium scitamineum Mating, Pathogenicity and Cell Wall Integrity

Abstract: The basidiomycetous fungus Sporisorium scitamineum causes a serious sugarcane smut disease in major sugarcane growing areas. Sexual mating is essential for infection to the host; however, its underlying molecular mechanism has not been fully studied. In this study, we identified a conserved farnesyltransferase (FTase) β subunit Ram1 in S. scitamineum . The ram1 Δ mutant displayed significantly reduced mating/filamentation, thus of weak pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 88 publications
2
21
1
Order By: Relevance
“…This confirms that S. scitamineum a locus gene SsMFA1 and SsPRA1 are functional in regulating fungal dimorphic switch, and likely acting at downstream of SsPrf1. This result is also consistent with a recent report on SsMFA1 characterization (Sun et al, 2019).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…This confirms that S. scitamineum a locus gene SsMFA1 and SsPRA1 are functional in regulating fungal dimorphic switch, and likely acting at downstream of SsPrf1. This result is also consistent with a recent report on SsMFA1 characterization (Sun et al, 2019).…”
Section: Resultssupporting
confidence: 94%
“…As reported in this study, we identified a Prf1 ortholog in S. scitamineum and found that it was responsible for both basal and pheromone-induced expression of mating type genes of the a1 locus. We further showed that deletion of the a locus gene SsMFA1 or SsPRA1 resulted in similar phenotype (Figure 6A) as the T-DNA insertion mutation or deletion mutant of the SsPRF1 gene (Figure 3A), as well as the reported MFA1 deletion phenotype (Sun et al, 2019). Our results provide new insight into the mechanism of pathogenicity of this important sugarcane pathogen, by confirming the biological function of the a 1 locus gene in S. scitamineum mating/filamentation, and indicating that SsPrf1 plays a key role in pheromone signaling and filamentous growth in S. scitamineum through transcriptional induction of the mating locus.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…After the gene was knocked out, the sexual mating ability of WT17 and WT18 was completely lost, and they were unable to infect sugarcane (Yan et al, 2016b). Sun et al (2019) found that the gene Ram1 encoding the farnesyltransferase (FTase) β-subunit in S. scitamineum through gene knockout and gene complement techniques was related to sexual mating, cell wall stability, and pathogenicity in S. scitamineum. Zhu et al (2020) reported that the pheromone response factor SsPRF1 was involved in the regulation of mycelial growth, sexual mating, and pathogenicity in S. scitamineum.…”
Section: Introductionmentioning
confidence: 99%